2014
DOI: 10.1016/j.biocel.2014.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Radiation persistently promoted oxidative stress, activated mTOR via PI3K/Akt, and downregulated autophagy pathway in mouse intestine

Abstract: While acute effects of toxic radiation doses on intestine are well established, we are yet to acquire a complete spectrum of sub-lethal radiation-induced chronic intestinal perturbations at the molecular level. We investigated persistent effects of a radiation dose (2 Gy) commonly used as a daily fraction in radiotherapy on oxidants and anti-oxidants, and autophagy pathways, which are interlinked processes affecting intestinal homeostasis. Six to eight weeks old C57BL/6J mice (n=10) were exposed to 2 Gy γ-ray.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 61 publications
3
45
0
Order By: Relevance
“…Reduced IGFBP3 along with increased pro-proliferative Ki67 staining in intestine and colon is in agreement with earlier observations reporting anti-proliferative and pro-apoptotic effects of IGFBP37677. Our observations in this study could act as the prelude necessary for future studies on contribution of leptin/IGF1 signaling axis to some of the heavy ion radiation’s long-term consequences such as premature senescence, metabolic alterations, and GI carcinogenesis we have reported previously413577879. The current study performed in wild type mice irradiated with a non-lethal dose of 56 Fe radiation is an initial step towards understanding GI tract related long-term hormonal alterations after heavy ion space radiation exposure especially after low dose exposures.…”
Section: Discussionsupporting
confidence: 93%
“…Reduced IGFBP3 along with increased pro-proliferative Ki67 staining in intestine and colon is in agreement with earlier observations reporting anti-proliferative and pro-apoptotic effects of IGFBP37677. Our observations in this study could act as the prelude necessary for future studies on contribution of leptin/IGF1 signaling axis to some of the heavy ion radiation’s long-term consequences such as premature senescence, metabolic alterations, and GI carcinogenesis we have reported previously413577879. The current study performed in wild type mice irradiated with a non-lethal dose of 56 Fe radiation is an initial step towards understanding GI tract related long-term hormonal alterations after heavy ion space radiation exposure especially after low dose exposures.…”
Section: Discussionsupporting
confidence: 93%
“…On one hand, mTOR is a key to cell growth and proliferation by promoting protein synthesis. On the other hand, recent work has demonstrated that mTOR is a crucial, negative regulator of autophagy in response to nutritional status, growth factor and stress signals (Jung et al, 2010; Datta et al, 2014). In AKI, the role of mTOR varies according to experimental models.…”
Section: Chemical Renoprotectantsmentioning
confidence: 99%
“…Mitochondria ROS act as essential signaling molecules in the regulation of the mitophagy and tumor development (71,72). Mitophagy is a process of mitochondria-selective autophagy in response to various signals, including oxidative stress, starvation, and modification of mitochondrial proteins (73). It has been shown that degradation of mitochondria and mtDNA can be executed by mitophagy.…”
Section: Mitochondrial Damage and Autophagymentioning
confidence: 99%